New DIW Berlin model can nowcast the current income distribution: Inequality likely to slightly increase in 2023 - Timm Bönke; Geraldine Dany-Knedlik; Laura Pagenhardt (DIW Weekly Report, 2023)
The unequal distribution of labor income in Germany is a hotly debated topic among policymakers and the general public alike. However, the relevant data for calculating the distribution is usually available with a delay of sometimes over two years. Accordingly, previous studies have only been about the past, not the current, distribution. Generally, the current development of the income distribution as well as the effects of current economic policy measures remain oblique. That is where DIW Berlin comes in: A new forecast model is making it possible to make statements about the current state of inequality in the monthly gross labor income of employees. To do so, a number of macroeconomic labor market variables, such as the share of people in short-time work as well as gross wages and salaries in various economic sectors, are combined with household-level data from the Socio-Economic Panel (SOEP). The calculations in this Weekly Report show that the forecast quality of the model is high. Thus, for the first time, insights into a longer period following the coronavirus pandemic can be gained: Following declining inequality up until 2021, primarily between 2010 and 2020, the new DIW Berlin model forecasts an interruption in the trend in 2022 and 2023. Overall, labor income inequality is predicted to have increased slightly over the course of the economic recovery following the pandemic and will be somewhat higher in 2023.
Keywords: E17; D31; E66; 330; Nowcast; income distribution; inequality